The spirit of Luc Boltanski : essays on the "pragmatic sociology of critique" - Susen, Simon; Turner, Bryan S. (Key issues in modern sociology., 2014)
What is the relevance of Luc Boltanski's 'pragmatic sociology of critique' to central issues in contemporary social and political analysis? In seeking to respond to this question, this book contains critical commentaries from prominent social theorists attempting to map out the influence and broad scope of Boltanski's oeuvre.